Igniter-induced hybrids in the 20-l sphere. (September 2017) - Taveau, J.R.; Going, J.E.; Hochgreb, S.; Lemkowitz, S.M.; Roekaerts, D.J.E.M.
Abstract: Dust explosibility is traditionally described by two parameters, namely the maximum explosion pressure, Pmax, and the deflagration index, KSt, usually determined through testing in a closed, pressure-resistant spherical vessel, either 20 L or 1 m 3 in volume. These parameters constitute key variables in the design of explosion protection systems, such as venting, suppression or isolation systems. The potential for overdriving dust combustion with pyrotechnical igniters in the 20-l sphere has been recognized, discussed and analyzed for many years, notably in the determination of the minimum explosible and limiting oxygen concentrations, which has led to specific guidelines regarding the ignition source strength in ASTM standards. The current paper presents new experimental evidence that the energy provided by pyrotechnical igniters may, in some instances, physically alter the dust being tested in the 20-l sphere. KSt values can be several times greater in the small vessel compared to those measured in the 1-m 3 chamber. Further visual evidence is provided to show that high energy ignition can produce a turbulent flame region, possibly consisting of a hybrid mixture of flammable gas (or vapor) and dust, which can propagate faster than the corresponding pure dust. The experiments suggest that KSt values measured in the 20-l sphere may no longer be representative of a dust deflagration in a real process environment. We recommend additional tests in a 1-m 3 chamber when a dust exhibits a low flash point, or when it's KSt is above 300 bar m/s in the 20-l sphere. Highlights: The high energy delivered by pyrotechnical igniters introduces bias in 20-l sphere dust explosibility measurements. Pyrotechnical igniters increase both the initial pressure and temperature prior to the actual flame propagation. Pyrotechnical igniters can alter dust samples and lead to the formation of a more reactive hybrid mixture. We propose to call this phenomenon an "igniter-induced hybrid". Deflagration indexes measured in our 20-l sphere experiments were 2 to 4 times greater than in the 1-m 3 chamber.